REPRESENTASI PERAN IBU DALAM IKLAN (ANALISIS SEMIOTIKA PADA IKLAN BERTEMA HARI IBU) - Mudafiuddin, Birda (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2020)
Advertising is a complex communication pattern that moves towards goals and uses strategies that influence the thoughts, feelings, and behavior of consumers. This study aims to describe the meaning of the Role of Mother contained in YouTube advertisements in December 2017 with the theme